KEPEMIMPINAN PEREMPUAN DALAM ISLAM - Dedi Sahputra Napitupulu; Salminawati Salminawati; Novita Sari (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2020)
This paper aims to find out how the Islamic view of women's leadership is. This paper uses the library study method of data gathering and information from various sources, such as books that contain a variety of theories that are needed researchers. The results of the study show that not only men can be leaders, but women can also be leaders. After Islam came the position of women was very glorified, respected, guarded, and guaranteed his life. The position of women according to Islamic legal views can be examined in various areas such as in the household, education field, skills field, political field, in the inheritance and in the field of worship.